Comparative effects of intraduodenal amino acid infusions on food intake and gut hormone release in healthy males. Issue 21 (15th November 2017) - Steinert, Robert E.; Ullrich, Sina S.; Geary, Nori; Asarian, Lori; Bueter, Marco; Horowitz, Michael; Feinle‐Bisset, Christine
Abstract: In contrast to the many studies of the effects of individual amino acids (AAs) on eating, no studies have compared the effects of different AAs on eating and underlying preabsorptive gastrointestinal mechanisms. To compare the effects of intraduodenal infusions ofl ‐tryptophan (TRP), l ‐leucine (LEU), l ‐phenylalanine (PHE) andl ‐glutamine (GLN) on appetite, gastrointestinal hormone responses (including ghrelin, cholecystokinin (CCK), peptide YY (PYY) and glucagon‐like peptide‐1 [GLP‐1]), glycemia (glucagon, insulin and glucose) and test meal size in healthy males, we retrospectively analyzed data from four published independent, randomized, double‐blind, placebo‐controlled studies of 90‐min intraduodenal infusions of the individual AAs. The designs of the studies were identical, except the dose of TRP (0.15 kcal/min) was lower than that of the other AAs (0.45 kcal/min) because higher doses of this AA were not well tolerated. TRP and LEU decreased intake more than PHE (reductions relative to control, ~219 ± 68, ~170 ± 48 and ~12 ± 57 kcal, respectively), and TRP decreased intake more than GLN (~31 ± 82 kcal). These effects of TRP and LEU versus GLN, but not versus PHE, were paralleled by greater decreases in plasma ghrelin, and increases in CCK, concentrations. TRP increased PYY more than GLN or LEU, but not PHE. LEU increased PYY less than PHE. No significant differences were detected for GLP‐1. PHE increased glucagon more than TRP or LEU, and increased insulin more than TRP. Under our experimental conditions, intraduodenal TRP and LEU were more satiating than PHE and GLN. The greater satiating efficacy of LEU versus PHE was significantly dissociated from the effects of these AAs on PYY, while the greater satiating potency of TRP versus PHE was significantly dissociated from the effects of these AAs on insulin and glucagon. In contrast, ghrelin and CCK, and potentially other mechanisms, including central sensing of individual AAs, appear to be stronger candidate mechanisms for the relative satiating effects obtained. Abstract : To better understand the relative effects of individual amino acids on eating, and to gain insights into the potential mechanisms that may lead to differential satiating effects, we compared the effects of premeal ID infusion of tryptophan (TRP), leucine (LEU), phenylalanine (PHE) or glutamine (GLN) on appetite, GI‐hormone responses, and meal size, using data from identically‐designed, randomized, double‐blind, placebo‐controlled tests that have in part been previously published. Under our experimental conditions, intraduodenal TRP and LEU were more satiating than PHE and GLN. The greater satiating efficacy of LEU versus PHE was significantly dissociated from the effects of these AAs on PYY, while the greater satiating potency of TRP versus PHE was significantly dissociated from the effects of these AAs on insulin and glucagon. In contrast, ghrelin and CCK, and potentially other mechanisms, including central sensing of individual AAs, appear to be stronger candidate mechanisms for the relative satiating effects obtained.